Sistem Informasi Pendaftaran Imunisasi Posyandu Melati Di Desa Air Merah Kabupaten Labuhanbatu Selatan Berbasis Web - Ladevi, Indah Frisky (Journal of Computer Science and Information System(JCoInS), 2021)
In this era of globalization, computers are needed in all aspects of life, including in the world of health. Just like the development of information systems. Exactly whether or not information depends on the information obtained. If the information produced is incomplete or incorrect, then it can be said that decision making will become incorrect and misdirected. Posyandu as a public health service, especially for baby's health, still has many weaknesses. In addition to requiring a long time in registration, the accuracy is also less acceptable. Registration of immunization is one of the initial processes before immunization. This immunization is one of the programs of the Posyandu, which is a way to prevent children from getting defects or deadly diseases in a cost effective manner. With the support of existing information technology, data processing currently carried out can be replaced with a web-based system. Data collection methods used are observation, interview, and literature study. The programming used is website programming using MySQL and PHP databases. This study produced a web-based infant immunization registration information system for the Melati Posyandu Labuhanbatu Selatan Red Water Village. Hopefully the existence of this information system can improve the work process of Posyandu cadres in handling the registration of babies who will be immunized.